Effects of eight weeks' continuous treatment with oral ranitidine and cimetidine on gastric acid secretion, pepsin secretion, and fasting serum gastrin. Issue 1 (January 1983) - Mohammed, R; Holden, R J; Hearns, J B; McKibben, B M; Buchanan, K D; Crean, G P
Abstract : Gastric acid secretion, pepsin secretion, and fasting serum gastrin levels were measured in 23 patients with duodenal ulcer disease, divided into three groups which received either cimetidine 800 mg daily, cimetidine 1600 mg daily, or ranitidine hydrochloride 300 mg daily for eight weeks. Pentagastrin tests were carried out at intervals both before and after treatment. Each dose of cimetidine reduced acid secretion to 42% of control one week after starting therapy. Ranitidine reduced acid secretion to 33% of the pretreatment value. Acid secretion remained suppressed to these levels throughout treatment with each drug. Acid secretion returned to pretreatment levels in all patients one week after treatment and remained normal until the end of the study. Both drugs reduced pepsin, which fell to 64% and 61% (p less than 0.01) after 800 mg and 1600 mg cimetidine respectively and to 65% (p less than 0.005) with ranitidine after one week's treatment. Pepsin secretion remained at this reduced level in both cimetidine groups till the end of treatment. Pepsin levels fell to 50% at two weeks of therapy with ranitidine but stabilised at this level till the end of therapy. Cimetidine withdrawal was followed by a return towards pretreatment levels of pepsin secretion; but secretion remained significantly depressed (p less than 0.05) to the end of the study period. In the ranitidine-treated patients pepsin output returned to normal after drug withdrawal. Fasting gastrin levels rose during treatment with both drugs but failed to reach significant levels. After withdrawal of treatment fasting serum gastrin levels returned to normal in all three groups of patients.